Efficiency of cell-based assays in detecting AChR antibodies in myasthenia gravis sera with low antibody concentrations as determined by radioimmunoprecipitation assay - Tzartos, John S.; Vakrakou, Aigli G.; Karagiorgou, Katerina; Zouvelou, Vasiliki; Chroni, Elisabeth; Damato, Valentina; Beretta, Francesca; Salakou, Stavroula; Sfyroera, Eirini; Veltsista, Dimitra; Voumvourakis, Konstantinos; Giannopoulos, Sotirios; et al. (Frontiers in Immunology, 2025)
ObjectivesWe investigated whether the acetylcholine receptor (AChR) cluster cell-based assay (CBA) is effective in detecting AChR antibodies in sera from myasthenia gravis (MG) patients with low antibody concentrations, as determined by radioimmunoprecipitation assay (RIPA).MethodsIn this retrospective diagnostic cohort study, 193 RIPA-positive sera from MG patients were analyzed. Following initial assessment using the gold-standard RIPA, samples were tested with a commercially available fixed CBA (F-CBA) and an in-house live CBA (L-CBA) to detect clustered AChR antibodies. Patients were classified into three groups based on RIPA levels to evaluate the sensitivity of each CBA. A subset of the cohort was blindly retested in a second laboratory to confirm results.ResultsThe sensitivity of L-CBA and F-CBA in detecting 36 sera with low AChR-antibody levels (1.0–2.8 nM) was relatively high for L-CBA (83.33%, 95% CI: 71.16%, 95.51%) and low for F-CBA (45.71%, 95% CI: 29.21% to 62.22%). Both CBAs were 100% sensitive for sera with AChR-RIPA values > 3 nM. Antibodies of RIPA+/CBA− sera could be immunoadsorbed on AChR-transfected cells equally well as those from RIPA+/CBA+ sera, indicating that CBA negativity was due to low antibody concentrations.DiscussionOverall, while AChR L-CBA demonstrates good sensitivity for detecting low concentrations of AChR antibodies, F-CBA performs less reliably in such cases. Since clustered AChR-CBAs can also identify antibodies that are not detectable by RIPA, we recommend that both RIPA and CBA be used together in the routine diagnosis of MG whenever possible. When available, L-CBA should be preferred over F-CBA due to its higher sensitivity.